The effect of cultivar, wilting and storage period on fermentation and the clostridial community of alfalfa silage. Issue 2 (3rd April 2018) - Zheng, Mingli; Niu, Dongze; Zuo, Sasa; Mao, Peichun; Meng, Lin; Xu, Chuncheng
Abstract: The objective of this study was to gain deeper insights into chemical transformations and the clostridial community dynamics during the ensiling of alfalfa. A factorial experiment was conducted with four alfalfa cultivars [Sanditi (A1), AC Caribou (A2), WL319HQ (A3) and 4030 (A4)] × three wilting durations [0 h (direct-cut), 2 h and 4 h] × three storage periods (14, 28 and 56 days). The clostridial community was examined using denaturing gradient gel electrophoresis. High butyric acid and ammonia nitrogen (NH3 –N) contents and clostridia numbers were observed in direct-cut silage, with higher values observed in A4 than in the other three cultivars. However, butyric acid and NH3 –N contents and clostridia numbers decreased with wilting regardless of the cultivar. Although Clostridium ghonii and Clostridium sartagoforme were common to all direct-cut and wilted silages, bands for these species were faint. Differences in the appearing time of these species were observed, bands for C. ghonii were found after 14 and 28 days of ensiling, while those for C. sartagoforme were only found after 56 days. In addition, in direct-cut silage, distinct bands for Clostridium perfringens were detected in A1, A2 and A3, while those for Clostridium sporogenes were detected in A4. The inactive spores of clostridia could be observed in 4-h wilted silage as no butyric acid was detected. It was concluded that the enhanced clostridial fermentation of direct-cut silage was attributed mainly to C. perfringens and C. sporogenes, while C. ghonii and C. sartagoforme were involved in the restricted clostridial fermentation of 2-h wilted silage.